THE EFFECT OF INDIVIDUAL COUNSELING WITH COGNITIVE RESTRUCTURING TECHNIQUES TO INCREASE THE RESILIENCE OF STUDENTS OF SMK NEGERI 4 BANDAR LAMPUNG - Sukaesih, Ena; Febriyani, Tika; Maharani, Laila (Universitas Pendidikan Mandalika, 2025)
Low resilience in students is a problem that hinders their ability to cope with life pressures and academic challenges. This condition is exacerbated by a negative mindset that makes it difficult for them to get up from difficulties. This study aims to analyze the influence of individual counseling with Cognitive Restructuring techniques in increasing the resilience of SMK Negeri 4 Bandar Lampung students. This technique helps individuals recognize, evaluate, and replace negative thoughts with positive, realistic mindsets. The study uses a quantitative approach with a Pre-Experimental One-Group Pretest-Posttest design. Data were collected through Likert scale questionnaires, structured interviews, and nonparticipant observations. The sample was purposively selected from 33 students of class X of DKV, with three students meeting the criteria of low resilience. Data analysis was conducted using the Wilcoxon Signed Rank Test. The results showed a significant increase in the level of resilience after the provision of individual counseling services with the Cognitive Restructuring technique. The results of the Wilcoxon test showed Z = -2.670 and Sig. (2-tailed) = 0.008 (< 0.05). The average resilience score increased from 96.67 (pretest) to 144 (posttest), then 156.67 (follow-up 1), and 169.33 (follow-up 2), indicating a high resilience category. Thus, individual counseling using Cognitive Restructuring techniques has been proven to be effective in helping students increase resilience, change negative mindsets, and strengthen mental resilience in the face of various pressures and challenges.